Current developments in management of human resources - Zamlynskyi, V.; Livinskyi, A.; Zakharkiv, I.; Korneeva, T.; Корнєєва, Т. С. (BA School of Business and Finance, 2021)
Modern socio-economic life requires research on the basic factors of development on the mission and values of the company, business reputation, brand, motivation, anti-crisis measures, corporate culture, effective communications as a set of human capital investments, which can be both the greatest value and the greatest risk, and their quality acts as a renovation element of enterprise management. In today's market situation, business reputation should become an integrative integrity and an important strategic asset, which is due to the growing importance of creating competitive advantages for the company through intangible assets, the growing importance of non-price competition, the role of personal ties, institutional and social investments, direct sales, knowledge and consumer confidence becomes the guarantor of a successful business.
Сучасні розробки в управлінні людськими ресурсами
Keywords: crisis communications management; optimization of business process; business reputation; corporate culture; goodwill; crisis communications; positioning; brand value; uncertainty; economic security; anti-crisis measures